Spin-Orbit Coupling Effects in Au 4f Core-Level Electronic Structures in Supported Low-Dimensional Gold Nanoparticles - Sahoo, Smruti R.; Ke, Shyue-Chu (Nanomaterials (Basel, Switzerland), 2021)
Despite their many advantages, issues remain unresolved over the variability in catalytic activities in supported gold nanoparticle (AuNP)-based catalysts, which requires precise characterization to unravel the presence of any fine features. Herein, upon analyzing the Au 4f core-level spin-orbit components in many as-synthesized AuNP-based catalysts, we observed that like deviations in the Au 4f7/2 binding energy positions, both the Au 4f7/2-to-Au 4f5/2 peak intensity and linewidth ratios varied largely from the standard statistical bulk reference values. These deviations were observed in all the as-synthesized supported AuNPs irrespective of different synthesis conditions, variations in size, shape or morphology of the gold nanoparticles, and different support materials. On the other hand, the spin-orbit-splitting values remained almost unchanged and did not show any appreciable deviations from the atomic or bulk standard gold values. These deviations could originate due to alterations in the electronic band structures in the supported AuNPs and might be present in other NP-based catalyst systems as well, which could be the subject of future research interest.